Budaya Senior-Yunior (Senpai-Kohai) dalam Struktur Masyarakat Jepang - Reny Wiyatasari (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
The purpose of this study is to describe the culture of senpai-kohai in a Japanese society system that has a vertical structure. The data used are several literature on Japanese seniority system (senpai-kohai) and interviews with several informants. The research method used is a qualitative-descriptive. Data collection with library studies, observations, and interviews to explore deeply about the experiences of informants related to seniority system in Japan. In analyzing data, researchers used the qualitative data analysis techniques. The results of this study show that the culture of senpai-kohai in the lives of Japanese people is reflected in the educational environment, club or organizational environment, work environment, and family environment. In addition to the family environment, senpai-kohai relations are shown through the attitude and actions of a senior to help, maintain, and guide his junior. Conversely, juniors also must behave in accordance with the guidance, instructions, and orders of their seniors. In addition, juniors must also respect and respect their seniors through the use of polite language (keigo) and keep his words